Estudio Investigativo para establecer los factores de éxito de los agronegocios aplicado a los mercados verdes, en pequeñas parcelas en el departamento del Quindío (2012)
Description: During the last decade, the agriculture sector in the Department of Quindío has had an economic, social and environmental development due to factors such as violence, forced displacement, economic crisis, food-borne diseases (ETA), misuse of natural resources, inconsistent agricultural practices and natural disasters that have decreased the agricultural production. This research study was done in order to improve the agrobusiness focusing on green markets since the small producers are the main beneficiaries. The type of study that was used was exploratory where the primary sources of information were small farmers from the region. They provided relevant information through surveys. Likewise, interviews were conducted by experts from different institutions that are related to the agricultural sector. All in all, there are six success factors that will help agribusiness enhance and move into green markets in the department of Quindio; as well as a paradigm shift, business culture, small farmers association, seals or ecological certifications, institutional support and the adjustment of financial institutions to small farmers reality.